A cut-off point in the Oxford Knee Score to identify patients with chronic pain after knee replacement - Pinedo-Villanueva, R; Khalid, S; Wylde, V; Gooberman-Hill, R; Judge, A (Springer, 2017)
We aimed to identify a cut-off point in the pain component subscale of the Oxford Knee Score (OKS) that could be used to identify patients with chronic pain 6 months after primary total knee replacement (TKR).